2021
DOI: 10.1002/fsn3.2474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymatic hydrolysis on physicochemical property and antioxidant activity of mulberry (Morus atropurpurea Roxb.) leaf protein

Abstract: Free radicals are highly reactive species that can induce fatty acid and lipid oxidation in food. This oxidation not only leads to the deterioration of quality attributes, such as flavor, aroma, texture, and color but also to loss of nutritive value and food spoilage. (Elias et al., 2008;Kou et al., 2013) In addition, free radical reactions can lead to the formation of reactive oxygen species (ROS), which play critical roles in various human diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
5
17
0
2
Order By: Relevance
“…A previous study on SGID of mulberry leaf protein and its neutrase hydrolysates found similar results (Sun et al. 2021 ). Further, the antioxidant activity of different molecular weight fractions indicated the lower fraction (< 3 kDa) exhibited the maximum activity, demonstrated with ORAC and TEAC assays.…”
Section: Discussionsupporting
confidence: 74%
“…A previous study on SGID of mulberry leaf protein and its neutrase hydrolysates found similar results (Sun et al. 2021 ). Further, the antioxidant activity of different molecular weight fractions indicated the lower fraction (< 3 kDa) exhibited the maximum activity, demonstrated with ORAC and TEAC assays.…”
Section: Discussionsupporting
confidence: 74%
“…The ratio of peptide bonds cleaved in a protein to the total number of peptide bonds during enzymatic hydrolysis is known as DH, which is an important measure of the degree of protein degradation . The reaction time of enzymatic hydrolysis is one of the main factors affecting DH . Flavourzyme has both endo- and exo-peptidase activities, which is specific for terminal hydrophobic amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…32 The reaction time of enzymatic hydrolysis is one of the main factors affecting DH. 33 Flavourzyme has both endo-and exo-peptidase activities, which is specific for terminal hydrophobic amino acids. It can effectively reduce the bitter taste of protein hydrolysates by cleaving the terminal hydrophobic amino acids.…”
Section: Optimization Of Hydrolysis Timementioning
confidence: 99%
“…Our previous study showed MP was mainly composed of proteins above 35 kDa (25%), proteins and polypeptides of 6.5 kDa–35 kDa (21%), and some small molecular peptides of 0.5 kDa–6.5 kDa [ 22 ]. To retain the main protein composition of MP, we chose the Amicon ® Ultra-15 centrifugal filter with 10 kDa and 30 kDa membranes as a segregator for separating the main proteins from the fractions below 10 kDa and 30 kDa (including small-molecular-weight saccharides and peptides), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, mulberry leaves are a rich source of protein (17–25% of dry weight) [ 21 ]. It has been reported that mulberry leaf protein (MP) has antioxidant activities [ 22 , 23 ]. According to our preliminary studies, MP was found to activate the immune response of RAW264.7 macrophages and significantly increase their pinocytosis capacity (see Figure S1 ).…”
Section: Introductionmentioning
confidence: 99%